Risk factors and long-term prognostic impact of immune related pancreatic injury in patients receiving immune checkpoint inhibitors - Akazawa, Yu; Nosaka, Takuto; Murata, Yosuke; Tanaka, Tomoko; Takahashi, Kazuto; Naito, Tatsushi; Ohtani, Masahiro; Nakamoto, Yasunari (Frontiers in Immunology, 2025)
BackgroundWith the widespread use of immune checkpoint inhibitors (ICIs), the management of immune-related adverse events (irAEs) has become increasingly important. ICI-induced pancreatic injury (ICI-PI) is rare, and its clinical characteristics remain unclear. This study aimed to clarify the risk factors for the development of ICI-PI and prognostic impact of ICI-PI.MethodsA total of 1039 patients with malignant tumors who received ICI therapy were recruited from September 2014 to December 2024 for this retrospective study. The clinical and pathological characteristics of ICI-PI, including risk factors and prognostic impact, were analyzed. The onset of ICI-PI and irAEs of other organs were defined according to CTCAE ver5.0. The pathological characteristics were evaluated using pancreatic tissue specimens obtained by endoscopic ultrasound-guided fine-needle biopsy.ResultsOf the 982 patients (703 males, 279 females; median age, 71.1 years) included in the study, 48 (4.9%) developed ICI-PI (Grades 2, 3, and 4 in 41, 3, and 4 cases, respectively), and 6 patients (0.6%) developed pancreatitis. Multivariate analysis revealed that the high serum amylase levels before ICI administration (odds ratio, 6.10; 95%CI, 2.55-14.6; P < 0.001) and the onset of irAE in other organs (odds ratio, 3.49; 95%CI, 1.88-6.49; P < 0.001) were independent risk factors for ICI-PI development. The incidence of other organ irAEs was significantly higher in the ICI-PI onset group than in the ICI-PI non-onset group (P < 0.001). Additionally, there was significantly better overall survival in the ICI-PI onset group than in the ICI-PI non-onset group (P < 0.001), which was corroborated by a landmark analysis. Also, pathological examination of ICI-related pancreatitis using multiplex fluorescence immunohistochemistry demonstrated infiltration of predominantly CD8 positive T lymphocytes contained abundant granzyme B into the pancreatic parenchyma.ConclusionsHigh serum amylase levels before ICI administration and development of other organ irAEs were identified as novel risk factors for ICI-PI onset, and the long-term prognosis was better in patients with ICI-PI. This finding suggests that thorough systemic management, including proactive evaluation of serum amylase levels and comprehensive monitoring for various irAEs, can contribute to early detection of ICI-PI, potentially leading to improved patient outcomes.